REVIEW OF RECOMMENDATIONS FOR THE MANAGEMENT OF POLYMYALGIA RHEUMATICA (ACR/EULAR 2015) - M. T. Vatutin; G. S. Smyrnova; G. G. Taradin; M. A. El-Khatib (Архивъ внутренней медицины)
Recommendations for the management of polymyalgia rheumatica are reflected in presented translation of new international guidelines (ACR/EULAR 2015).